Abscisic acid‐dependent PMT1 expression regulates salt tolerance by alleviating abscisic acid‐mediated reactive oxygen species production in Arabidopsis. Issue 9 (1st August 2022) - He, Qi Yu; Jin, Jian Feng; Lou, He Qiang; Dang, Feng Feng; Xu, Ji Ming; Zheng, Shao Jian; Yang, Jian Li
Abstract: Phosphocholine (PCho) is an intermediate metabolite of nonplastid plant membranes that is essential for salt tolerance. However, how PCho metabolism modulates response to salt stress remains unknown. Here, we characterize the role of phosphoethanolamine N‐ methyltransferase 1 (PMT1) in salt stress tolerance in Arabidopsis thaliana using a T‐DNA insertional mutant, gene‐editing alleles, and complemented lines. The pmt1 mutants showed a severe inhibition of root elongation when exposed to salt stress, but exogenous ChoCl or lecithin rescued this defect. pmt1 also displayed altered glycerolipid metabolism under salt stress, suggesting that glycerolipids contribute to salt tolerance. Moreover, pmt1 mutants exhibited altered reactive oxygen species (ROS) accumulation and distribution, reduced cell division activity, and disturbed auxin distribution in the primary root compared with wild‐type seedlings. We show that PMT1 expression is induced by salt stress and relies on the abscisic acid (ABA) signaling pathway, as this induction was abolished in the aba2‐1 and pyl112458 mutants. However, ABA aggravated the salt sensitivity of the pmt1 mutants by perturbing ROS distribution in the root tip. Taken together, we propose that PMT1 is an important phosphoethanolamine N‐ methyltransferase participating in root development of primary root elongation under salt stress conditions by balancing ROS production and distribution through ABA signaling. Abstract : In Arabidopsis, salt stress induced abscisic acid‐dependent expression of PHOSPHOETHANOLAMINE N‐METHYLTRANSFERASE 1 (PMT1), which contributes to maintaining primary root elongation by alleviating plasma membrane damage caused by salt‐induced reactive oxygen species, reduced cell division, and disturbance of auxin distribution.